2014
DOI: 10.1371/journal.pone.0109479
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry-Based Metabolite Profiling in the Mouse Liver following Exposure to Ultraviolet B Radiation

Abstract: Although many studies have been performed on the effects of ultraviolet (UV) radiation on the skin, only a limited number of reports have investigated these effects on non-skin tissue. This study aimed to describe the metabolite changes in the liver of hairless mice following chronic exposure to UVB radiation. We did not observe significant macroscopic changes or alterations in hepatic cholesterol and triglyceride levels in the liver of UVB-irradiated mice, compared with those for normal mice. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Today, such mass spectral libraries can be created by applying rules of fragmentation patterns on large in silico structure list, as we have previously shown for over 200,000 mass spectra in LipidBlast [ 2 ] for twenty-six common lipid classes such as (lyso) phosphatidylcholines, monogalactosyldiacylglycerols or triacylglycerols. LipidBlast itself has been applied for the annotation of lipids in mouse liver [ 3 ], rat urine/serum [ 4 ] and in various algae species [ 5 , 6 ], demonstrating that this strategy enables rapid annotation of many molecular species from mass spectra [ 7 ]. LipidBlast templates use heuristic information of MS/MS fragmentation patterns to extend the range of in silico predicted mass spectra that can be used to discover species of novel lipid classes.…”
Section: Introductionmentioning
confidence: 99%
“…Today, such mass spectral libraries can be created by applying rules of fragmentation patterns on large in silico structure list, as we have previously shown for over 200,000 mass spectra in LipidBlast [ 2 ] for twenty-six common lipid classes such as (lyso) phosphatidylcholines, monogalactosyldiacylglycerols or triacylglycerols. LipidBlast itself has been applied for the annotation of lipids in mouse liver [ 3 ], rat urine/serum [ 4 ] and in various algae species [ 5 , 6 ], demonstrating that this strategy enables rapid annotation of many molecular species from mass spectra [ 7 ]. LipidBlast templates use heuristic information of MS/MS fragmentation patterns to extend the range of in silico predicted mass spectra that can be used to discover species of novel lipid classes.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics is a powerful tool to study post-radiation changes in metabolism and bioenergetics even before the onset of clinical symptoms and can augment triage of an exposed population in real-life scenarios 19,20 . Past metabolomics analysis investigated mouse 21 and rat 22 urine, rat plasma 23 , and mouse livers 24,25 . In 2013, we reported for the first time radiation-induced metabolite changes in the GI tissues of mice using ultraperformance liquid chromatography (UPLC) coupled with Time-of-flight mass spectrometry (TOF-MS) 20 .…”
mentioning
confidence: 99%
“…Because the CFLs, emits ultraviolet radiation spatially UVA, UVB and even UVC (1,4). Many studies have shown that UV radiation can cause DNA damage, cellular aging, oxidative damage, production of free radicals, and tumor formation (2,15). A recent study reported that UV radiation changes oxidative stressrelated biomarker in the liver (11) due to the fact that the oxidative stress is due to over production of reactive oxygen species that can induce oxidative damage to vital cellular molecules and structures (24).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that UVB and UVA emitted by CFLs increased the level of serum ALT, AST, and cholesterol, as well as appearance changes of liver in wistar rats (not published). The liver is the largest solid organ of the body and plays a crucial role in humans and animals lives due to the fact that it performs numerous essential tasks including: regulates the levels of most chemicals in the blood, excretes bile, detoxifies harmful compounds, and supports the function of other organs in the body, thus helping homeostasis (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%